Manajemen Kecerdasan Spiritual Dalam Menyikapi Paham Radikalisme Di Indonesia - ARMAN ARMANSYAH FUDIN (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2018)
Management is the science of regulating or influencing others to achieve the stated goals. Good management will create a great change in the business carried out, social conditions, and also personal changes. Good management of self will increase the intelligence possessed. One of them is spiritual intelligence. Spiritual intelligence is an effort to direct every action taken to always follow his personal abilities that have transcendent skills, as well as a great awareness to pass through life by using spiritual knowledge to find a way out about life's problems. One of the problems of life that develops in society is the circulation of extreme and negative understandings. One of them is radicalism. Radicalism in Indonesia has developed since the Dutch colonialism, and is increasingly fertile after the fall of the New Order regime. The proliferation of radicalism in Indonesia is influenced by the lack of spiritual awareness possessed. As a result the doctrines are easy to enter, one of them is the doctrine of jihad. Furthermore, radicalism is influenced by globalization and education. The effects of this radicalism cause unrest in the community. For this reason, serious efforts are needed in addressing this radicalism, both from the government, scientists and society in general. Therefore, effective management is needed to address radicalism that is flourishing in the community. One of them is the management of spiritual intelligence. The process of building spiritual intelligence management can be done by providing guidance, such as teaching the Koran, practicing prayer, practicing fasting, practicing Hajj and utilizing the method of the Prophet's preaching, namely exemplary approach, maximizing time utilization, fair attitude, praying kindness, activate the potential for thinking and developing mentally. Furthermore in education by providing moral education, which includes habituation, understanding of which good and bad deeds, assignments in which there is reproof, mental cleansing or the soul of all evil and despicable deeds, as well as the obligation to live morally. Key words: Management, Spiritual Intelligence, Radicalism